2021
DOI: 10.3390/app112110077
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Tumors: Phytochemical and Drug Combinations Targeting the Hallmarks of Cancer

Abstract: Cancer is a worldwide burden resulting in millions of deaths each year. In particular, gastrointestinal tumors are life-threatening malignancies and one of the leading reasons for death in developed countries. Phytochemicals can be found in grains, vegetables, fruits and several foods. Many phytochemicals, such as curcumin, genistein, luteolin, vitexin-2-O-xyloside, avenanthramides, quercetin, epigallocatechin-3-gallate (EGCG), resveratrol, sulforaphane, piperine and thymoquinone have been used in combination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 158 publications
(201 reference statements)
0
2
0
Order By: Relevance
“…The studies reported in the present review indicate that flavonoids appear to be useful functional food compounds, in the prevention of some chronic pathological conditions 131,132 . In particular, experimental in vitro and in vivo investigations indicate that citrus flavonoids may play an important role in the prevention and treatment of atherosclerosis and human tumors 133,134,135 . Besides vitamin C, folate, dietary fiber and carotenoids 136 , the beneficial effects of diet citrus fruits can be attributed, in particular, to the antioxidant activity of flavonoids present in citrus fruit.…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 99%
“…The studies reported in the present review indicate that flavonoids appear to be useful functional food compounds, in the prevention of some chronic pathological conditions 131,132 . In particular, experimental in vitro and in vivo investigations indicate that citrus flavonoids may play an important role in the prevention and treatment of atherosclerosis and human tumors 133,134,135 . Besides vitamin C, folate, dietary fiber and carotenoids 136 , the beneficial effects of diet citrus fruits can be attributed, in particular, to the antioxidant activity of flavonoids present in citrus fruit.…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 99%
“…However, cancer treatments have mostly relied on specific cytotoxic chemotherapy, and their impact on dividing healthy cells results in adverse side effects. There is a renewed interest in natural compounds that can inhibit the growth and metastasis of cancer, and investigations of their adjuvant effects with traditional chemo-drugs are underway [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%